2013
DOI: 10.1002/jgt.21711
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Sparse Graphs into Forests and a Graph with Bounded Degree

Abstract: For a loopless multigraph G, the fractional arboricity Arb(G) is the maximum of |E(H)||V(H)|−1 over all subgraphs H with at least two vertices. Generalizing the Nash‐Williams Arboricity Theorem, the Nine Dragon Tree Conjecture asserts that if Arb (G)≤k+dk+d+1, then G decomposes into k+1 forests with one having maximum degree at most d. The conjecture was previously proved for (k,d)∈{(1,1),(1,2)}; we prove it for d=k+1 and when k=1 and d≤6. For (k,d)=(1,2), we can further restrict one forest to have at most tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…They proved this for k = 1 when d ∈ {1, 2}. In [16], it was proved also for d = k + 1 and for k = 1 when d ≤ 6.…”
Section: Introductionmentioning
confidence: 74%
“…They proved this for k = 1 when d ∈ {1, 2}. In [16], it was proved also for d = k + 1 and for k = 1 when d ≤ 6.…”
Section: Introductionmentioning
confidence: 74%
“…Partial results towards this weaker conjecture are obtained in [7,1,6]. Recently, for ǫ ≥ 1 2 , Conjecture 2 was shown to be true by Kim et al [4], but the case ǫ < 1 2 remains open (there are some special values for which it is known, see [4]). Our main result is the following theorem which almost proves Conjecture 2.…”
Section: Conjecturementioning
confidence: 85%
“…However, this is less interesting because in this case Conjecture 2 itself has been proved in [4], so we only sketch the proof at the end of Section 3.…”
Section: Relation To Degree Bounded Matroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the progress of Nine Dragon Tree (NDT) Conjecture, in [7], Montassier et al proved the cases of (k, d) * = (1, 1) and (k, d) * = (1, 2), and they showed that no larger value of γ f (G) is sufficient; in [6], Kim et al proved the cases of (k, d) * = (k, k + 1) and…”
Section: E(g[x])|mentioning
confidence: 98%